Trisacryl Gelatin Microembolism and Metastases in the Lung after Renal Artery Embolization and Nephrectomy for Renal Cell Carcinoma - Andres Borja Alvarez; Jack P. Leventhal; Cherise Cortese; Barbara L. McComb; David D. Thiel; Andras Khoor (Case Reports in Urology)
This is the first report, to our knowledge, of widespread, histologically confirmed trisacryl gelatin pulmonary microembolism after renal artery embolization (RAE). In addition, this is the first report of lung involvement by both metastatic renal cell carcinoma (RCC) and an embolic agent used for RAE. The patient was a 63-year-old woman who recently presented with both dyspnea on exertion and productive cough. Her past medical history included clear cell RCC, which was treated with preoperative trisacryl gelatin microsphere RAE and right nephrectomy 9 years earlier. Computed tomography of the chest showed multiple lung nodules, a mass-like density in the left lower lobe, and mediastinal and hilar lymphadenopathy. Wedge resections of the lung showed multiple foci of metastatic RCC and extensive involvement of the muscular pulmonary arteries by trisacryl gelatin microspheres.